PLANNING AND APPLICATION OF METHODS IN DIFFERENTIATED INSTRUCTION AND INDIVIDUAL APPROACH TO PUPILS WITH DIFFICULTIES IN PRIMARY SCHOOL - Kudek Mirošević, Jasna; Radetić Paić, Mirjana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In an inclusive school teachers are expected to take responsibility for planning the teaching process in which they will apply adequate support (Ahon Adaka, 2013; Tomlinson, 2015). The aim of this research is to determine certain specificities of teachers’ differentiated instruction in their teaching and planning of individualised methods for the successful conduction of activities with pupils with difficulties in lower and higher grades of primary school. The set hypothesis states that there is a statistically significant difference between class teachers and subject teachers of primary schools of the Republic of Croatia (N=410) in the estimation of their own planning and application of methods in differentiated instruction and individualised approach to pupils with difficulties. The nonparametric Mann-Whitney U test was used to test the differences between teachers groups. The results showed that class teachers applied methods relating to pupils’ more successful inclusion in activities and supported their individuality by applying individualised teaching aids more than subject teachers. Such results indicate that differentiated and individualised teaching methods which are most adequate for a certain pupil and which will support their self-activity during primary education are still insufficiently present, even more in higher grades of primary school.